Genetic assignment of fisheries bycatch reveals disproportionate mortality among Alaska Northern Fulmar breeding colonies. (4th March 2022) - Baetscher, Diana S.; Beck, Jessie; Anderson, Eric C.; Ruegg, Kristen; Ramey, Andrew M.; Hatch, Scott; Nevins, Hannah; Fitzgerald, Shannon M.; Carlos Garza, John
Abstract: Global fisheries kill millions of seabirds annually through bycatch, but little is known about population‐level impacts, particularly in species that form metapopulations. U.S. North Pacific groundfish fisheries catch thousands of Northern Fulmars ( Fulmarus glacialis rodgersii ) each year, making fulmars the most frequently caught seabird in federally managed U.S. fisheries. Here, we used genetic stock identification to assign 1, 536 fulmars sampled as bycatch to one of four Alaska breeding colonies and quantified the similarity of bycatch locations at sea among colonies. We found disproportionately high bycatch from the Pribilof Islands (6% of metapopulation, 23% of bycatch), and disproportionately low bycatch from Chagulak Island (34% of metapopulation, 14% of bycatch). Overlap between fisheries and colony‐specific foraging areas diverge more during the summer breeding season, leading to greater differences in bycatch susceptibility. Contemporary and historical gene flow likely contributes to low genetic differentiation among colonies (FST = 0.003–0.01), yet these values may not represent present connectivity. Our findings illustrate how genetic stock identification can link at‐sea threats to colonies and inform management to reduce bycatch from impacted colonies.